RETRACTED: A Green Synthesis Strategy of Binuclear Catalyst for the C-C Cross-Coupling Reactions in the Aqueous Medium: Hiyama and Suzuki–Miyaura Reactions as Case Studies - Ghamari Kargar, Pouya; Bagherzade, Ghodsieh (Frontiers in Chemistry, 2021)
Cellulose, as a green and available phytochemical, was immobilized on the surface of magnetite nanoparticles then doped with imidazole and Co complex (Fe3O4@CNF~ImSBL~Co) and used as a water-dispersible, recyclable and efficient nano catalyst for the synthesis of C−C cross-coupling reactions including fluoride-free Hiyama and Suzuki reactions in an aqueous medium as an efficient and vital solvent, due to their high application and importance in various fields of science. Different spectroscopic and microscopic techniques were used for the catalyst characterization such XRD, FESEM, TEM, FT-IR, EDX, DLS, VSM, UV-Vis, and ICP analyses. The presence of imidazole as ionic section tags with hydrophilic character on the Co-complex supported on magnetic nanoparticles provides dispersion of the catalyst particles in water, which leads to both higher catalytic performance and also facile catalyst recovery and reuse six times by successive extraction and final magnetic separation. High catalytic activity was found for the catalyst and high to excellent efficiency was obtained for all Suzuki (80–98% yield; E factor: 1.1-1.9) and Hiyama (87–98% yield; E factor: 0.26-1.1) derivatives in short reaction times under mild reaction conditions in the absence of any hazardous or expensive materials. There is not any noticeable by-product found whether for Suzuki or Hiyama derivatives, which reflects the high selectivity and also the lower the E factor the more favorable is the process in view of green chemistry. The bi-aryls were achieved from the reaction of various aryl iodides/bromides and even chlorides as the highly challenging substrates, which are more available and cheaper, with triethoxyphenylsilane or phenylboronic acid. To prove the performance of the catalyst components (synergistic of SBL~Co and IL), its different homologs were incorporated individually and studied for a model reaction. Exclusively, this is an introductory statement on the use of Cobalt binuclear symmetric ionic liquid catalysts in Hiyama reactions.